2007
DOI: 10.1080/17421770701348198
|View full text |Cite
|
Sign up to set email alerts
|

Low Pay, Higher Pay and Job Satisfaction in Wales

Abstract: Using the first six waves of the Welsh boosts to the British Household Panel Survey this paper attempts to explain the determinants of overall job satisfaction and four facets of job satisfaction in Wales, distinguishing between female and male workers and low-paid and higher paid workers. The motivation of the paper is the claim made widely in the EU that low-paid jobs are jobs of inherently low quality, in which case we should expect that job satisfaction would be lower in low-paid jobs. Since there are prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Using data from the British Household Panel Survey (BHPS), Leontaridi and Sloane (2001) and Leontaridi, Sloane and Jones (2005) have shown that low-paid workers in the United Kingdom actually enjoy greater job satisfaction than their higher-paid counterparts. Jones and Sloane (2007) also find that mean job satisfaction in the low-wage economy of Wales is not lower than in the rest of the United Kingdom. These studies led to the conclusion that there is no justification for the European Commission's assertion that low-paid jobs are inherently jobs of low quality, at least as far as the British evidence is concerned.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Using data from the British Household Panel Survey (BHPS), Leontaridi and Sloane (2001) and Leontaridi, Sloane and Jones (2005) have shown that low-paid workers in the United Kingdom actually enjoy greater job satisfaction than their higher-paid counterparts. Jones and Sloane (2007) also find that mean job satisfaction in the low-wage economy of Wales is not lower than in the rest of the United Kingdom. These studies led to the conclusion that there is no justification for the European Commission's assertion that low-paid jobs are inherently jobs of low quality, at least as far as the British evidence is concerned.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Hal ini menunjukkan bahwa kepuasan gaji merupakan prediktor komitmen pada organisasi. Sebagaimana penelitian Jones & Sloane (2007) bahwa aras gaji memengaruhi kepuasan kerja karyawan. Trochim (2006) juga menerangkan bahwa kepuasan gaji merupakan salah satu faktor yang memengaruhi kepusan kerja.…”
Section: Model Penelitianunclassified
“…Valiéndose de datos de la encuesta del Panel de Hogares del Reino Unido (BHPS), Leontaridi y Sloane (2001) y Leontaridi y otros (2005) han demostrado que los trabajadores con salario bajo de ese país gozan en realidad de más satisfacción en su trabajo que sus homólogos mejor remunerados. Jones y Sloane (2007) también constataron que la satisfacción media con el trabajo en la economía de bajos salarios del País de Gales no es inferior a la del resto del Reino Unido. En esos estudios se llegó a la conclusión de que no está justificada la afirmación de la Comisión Europea de que los trabajos con remuneración baja son intrínsecamente de mala calidad, al menos según las pruebas recogidas en el Reino Unido.…”
Section: Análisis De La Bibliografía Especializadaunclassified